Perancangan Sistem Informasi Akuntansi Laporan Keuangan Standar PSAK 45s - Lita Lara Rosita (Labkat Press KA FTIK UNIKOM, 2018)
The time of managing financial reporting is still done by making the calculation in the MS. Excel, so that the accounting records in the Treasurer is less effective at generating financial reports quickly and accurately. As well as financial statements have not been fully made use of accounting standards in force in Indonesia. To these problems, the writer took the title